TRANSFORMING PUBLIC SERVICES: THE ROLE OF DIGITAL INNOVATION IN INDONESIAN MUNICIPAL GOVERNANCE - Afrilia, Ufa Anita; Asy'Ary, Ayuningtiyas Putri Mumpuni Halim; Muhdiarta, Untung; Mayasari, Yane; Anangkota, Muliadi (Alqaprint Jatinangor, 2024)
Digital innovation has become an important catalyst in the transformation of public services in Indonesia, especially at the local government level. The application of digital technology can increase transparency, accountability, and responsiveness of the government to the needs of the community. However, challenges such as infrastructure gaps and bureaucratic resistance are still major obstacles in this process. This study aims to explore the impact of digital innovation on the quality of public services in local governments. The study was conducted using a qualitative approach, using thematic analysis of data obtained from various relevant sources. The results of the study indicate that digital innovation significantly improves the quality of public services by accelerating the administrative process and increasing transparency and accountability. Digital technology also enables local governments to be more responsive to community needs and encourages public participation in decision-making. However, the success of digital transformation is highly dependent on leadership commitment, technological infrastructure development, and increased human resource capacity. Challenges such as technological gaps between regions and bureaucratic resistance need to be overcome so that digital innovation can be implemented effectively. With the right strategy, digital innovation has great potential to increase efficiency and public trust in government in Indonesia.